2020
DOI: 10.1101/2020.07.02.184325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A computational exploration of resilience and evolvability of protein-protein interaction networks

Abstract: AbstractProtein-protein interaction (PPI) networks represent complex intra-cellular protein interactions, and the presence or absence of such interactions can lead to biological changes in an organism. Recent network-based approaches have shown that a phenotype’s PPI network’s resilience to environmental perturbations is related to its placement in the tree of life; though we still do not know how or why certain intra-cellular factors can bring about … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…A key feature providing resilience to interacting networks is self-regulation within modules, while interactions among them might decrease resilience (but see ref. 79 ). One could therefore ask how these two fundamental quantities change during aging.…”
Section: Resilience and Critical Transitions: Legacies From Theoretic...mentioning
confidence: 99%
“…A key feature providing resilience to interacting networks is self-regulation within modules, while interactions among them might decrease resilience (but see ref. 79 ). One could therefore ask how these two fundamental quantities change during aging.…”
Section: Resilience and Critical Transitions: Legacies From Theoretic...mentioning
confidence: 99%
“…In economics, more open and wealthy countries are more likely to make stronger international ties and have the capacity to maintain more ties. For an example in biology, recent computational experiments indicate plausibility that gene-expression (which influences the concentration of proteins within cells) may aid in the formation of protein-protein interaction networks 21 . In each case, the collection of tendencies to make links of each node will form some kind of distribution.…”
Section: Theorymentioning
confidence: 99%
“…Compacting a set of possible states is ubiquitously found in various biological system, such as biochemical network and neural network. It is shown that biological real networks are very sparse, compared to complete network [27,28]. However, it is overlooked that even a sparse network is perpetually changed through time, not to be fallen into the steady state.…”
Section: Model Reproduction Of Chemical Inhibitorsmentioning
confidence: 99%